Endoplasmic Reticulum Stress Activation in Alport Syndrome Varies Between Genotype and Cell Type - Wang, Cong; Liang, Shenghui; Xing, Shijia; Xu, Ke; Xiao, Huijie; Deng, Haiyue; Wang, Xiaoyuan; Chen, Liangyi; Ding, Jie; Wang, Fang (Frontiers in Genetics, 2020)
Alport syndrome is a hereditary progressive chronic kidney disease caused by mutations in type IV collagen genes COL4A3/4/5, in which X-linked Alport syndrome (XLAS), leaded by COL4A5 gene mutations of COL4A5, is the most-common form of Alport syndrome. A strong correlation has been found between COL4A5 mutation type and the age developing end-stage renal disease in male patients. Mutant a (IV) chain can retain in the endoplasmic reticulum lumen, then cause endoplasmic reticulum stress (ERS), subsequently exerting deleterious intracellular effects through the activation of ERS. Nonetheless, the exact beginning time that mutant type IV collagen a chain exerting its deleterious effects remains elusive. In this study, we aimed to explore the relationship between COL4A5 genotype and cell type in ERS activation, we obtained skin fibroblasts from Alport syndrome patients with different COL4A5 mutation categories [including a missense mutation (c.4298G＞T, p.Gly1433Val) in exon 47, a splicing mutation (c.1949-1G＞A) in intron 25, and an insertion (c.573-c.574insG, p. Pro193Alafs*23) in exon 10] and then reprogrammed them into induced pluripotent stem cells (iPSCs). It is interesting to note that no significant dysregulation of ERS pathway markers were observed in three COL4A5 mutant iPSCs, however, we observed the significant activation of ERS at COL4A5 mutant fibroblasts. Besides, we also found that the activation levels of some ERS markers in fibroblasts with three COL4A5 mutation types is not exactly the same as the others. It is demonstrated that mutant COL4A5 protein have different effect on cells at different stages of ontogenesis, providing a theoretical basis for choosing the timing of intervention. Besides, the different activation of ERS in fibroblasts may contribute to the intracellular molecular mechanisms for the correlation between genotype and clinical features in X-linked Alport syndrome